Topical minoxidil-loaded nanotechnology strategies for alopecia - Santos, AC (2020)
Androgenetic alopecia (AGA) is a multifactorial and age-related condition characterized by substantial hair loss affecting both men and women. Conventional treatments include the use of topical minoxidil (MNX) formulations to stimulate hair growth and restore hair condition. However, those treatments are associated with limited performance and a lack of tolerability and compliance due to the emergence of adverse effects. Considering that the development of nanotechnology-based formulations as hair loss therapeutic strategies has been clearly growing, topical MNX delivery by means of these innovative formulations is known to enhance MNX skin permeation and depot formation into hair follicles, allowing for MNX-controlled release, increased MNX skin bioavailability and enhanced therapeutic ecacy with minimal adverse effects. This review highlights the potential of nanotechnology-based MNX delivery formulations for improved hair loss therapeutics, including a thorough assessment of their in vitro and in vivo performances, as well as regulatory and nanosafety considerations.